Servant Leadership of Principals and Its ‎Relationship to Teachers’ Morale - Al-Anezi, Ahmad (Jordan Journal of Educational Sciences, 2021)
The study aimed to identify the degree of practice of school principals of servant leadership and its relationship to teachers’ morale from the perspective of middle-school teachers in Kuwait. The study applied the descriptive-analytical and correlation methods and the sample was chosen using stratified random sampling and consisted of (353) teachers. The study concluded a number of results: The responses of the sample towards the servant leadership and its dimensions were all high (where the altruism dimension was recorded first, followed by love, then humility, and finally, empowerment); There were no significant differences due to gender, in the dimensions of altruism and humility, in favor of females; there were no significant differences due to the level of education and teaching experience; there were significant differences due to the scientific department’s specialization in humility, in favor of literary subjects; the responses of the sample towards the teachers’ morale were high; there was a positive relatioship between servant leadership and its four dimensions and teachers’ morale